Vaccination with an HIV T-cell immunogen induces alterations in the mouse gut microbiota - Alessandra Borgognone; Aleix Elizalde-Torrent; Maria Casadellà; Luis Romero; Tuixent Escribà; Mariona Parera; Francesc Català-Moll; Marc Noguera-Julian; Christian Brander; Alex Olvera; Roger Paredes (npj Biofilms and Microbiomes, 2022)
Abstract The gut microbiota is emerging as a crucial factor modulating vaccine responses; however, few studies have investigated if vaccines, in turn, can alter the microbiota and to what extent such changes may improve vaccine efficacy. To understand the effect of T-cell vaccination on the gut microbiome, we administered an HIV-1 T-cell immunogen (HTI arm) or PBS (control, Mock arm) to C57Bl/6 mice following a heterologous prime-boost scheme. The longitudinal dynamics of the mice gut microbiota was characterized by 16 S ribosomal RNA sequencing in fecal samples collected from cages, as well as from three gut sections (cecum, small and large intestine). Serum and spleen cells were obtained at the last time point of the study to assess immune correlates using IFNγ ELISPOT and cytokine Luminex® assays. Compared with Mock, HTI-vaccinated mice were enriched in Clostridiales genera (Eubacterium xylanophilum group, Roseburia and Ruminococcus) known as primary contributors of anti-inflammatory metabolites, such as short-chain fatty acids. Such shift was observed after the first HTI dose and remained throughout the study follow-up (18 weeks). However, the enriched Clostridiales genera were different between feces and gut sections. The abundance of bacteria enriched in vaccinated animals positively correlated with HTI-specific T-cell responses and a set of pro-inflammatory cytokines, such as IL-6. This longitudinal analysis indicates that, in mice, T-cell vaccination may promote an increase in gut bacteria known to produce anti-inflammatory molecules, which in turn correlate with proinflammatory cytokines, suggesting an adaptation of the gut microbial milieu to T-cell-induced systemic inflammation.